Toward the Implementation of an ASIC-Like System on FPGA for Real-Time Video Processing with Power Reduction - Lilia Kechiche; Lamjed Touil; Bouraoui Ouni (International Journal of Reconfigurable Computing)
Driven by the importance of energy consumption in system-on-chip design as an evaluation factor, this paper presents a design methodology at the system level to optimize power consumption on ARM-based architecture for real-time video processing. The proposed design flow is based on the interaction between the tool and user optimizations. The tool optimizations are the options and best practices available on the integrated design environment for the Xilinx technology and the target Zynq-7000 architecture. The user methods present methods proposed by the user to optimize power consumption. We used the principles of voltage scaling and frequency scaling techniques for user methods. These two techniques allow energy to be consumed in the proportion of work to be done. The suggested flow is applied on real-time video processing system. The results show power savings for up to 60% with respect to performance and real-time constraints.